TAD Click Chemistry on Aliphatic Polycarbonates: A First Step Toward Tailor‐Made Materials. Issue 7 (11th January 2019) - Baroni, Alexandra; Vlaminck, Laetitia; Mespouille, Laetitia; Prez, Filip Du; Delbosc, Nicolas; Blankert, Bertrand
Abstract : For the first time, the effectiveness of triazolinedione (TAD) click chemistry onto aliphatic polycarbonates (APC) is demonstrated. Statistic copolymers carrying click‐reactive conjugated diene (in a ratio of 10%) are synthesized via organocatalyzed ring‐opening polymerization. The highly efficient click reaction of TADs carrying simple butyl and phenyl functions are confirmed by 1 H‐NMR and DSC. Network formation using a bivalent TAD is also performed and simply characterized by DSC. This post‐polymerization functionalization of biocompatible and biodegradable APC pave the way to easy and versatile "on‐demand" materials design. Abstract : This proof of concept of triazolinedione (TAD) click chemistry onto biodegradable and biocompatible aliphatic polycarbonates paves the way of versatile and easy on‐demand functionalization. For the first time, a cyclic carbonate carrying click‐reactive conjugated diene is copolymerized via organocatalyzed ring‐opening polymerization, followed by click reaction of TAD moieties.